Constituents, morphological and thermal stability characteristics of wood ash and wood charcoal microparticles for composites application - Oladele, Isiaka Oluwole; Ajayi, Mathew A.; Taiwo, Anuoluwapo Samuel; Ajileye, Joshua Oluwatobi; Oyegunna, Seun Ayodeji; Orisawayi, Abimbola Oluwatayo (Elsevier, 2025)
This research investigates the physicochemical properties of wood ash and wood charcoal, two by-products derived from the pyrolysis of wood, focusing on their potential applications as sustainable reinforcement materials in composite manufacturing. Through a systematic characterisation process, we analysed both materials' chemical composition, thermal stability, crystallographic structure, and surface morphology. The findings reveal that wood ash is rich in calcium and magnesium oxides, which enhance its mechanical properties and reactivity, making it an effective additive in composite formulations. Moreover, wood charcoal exhibits a high carbon content and specific surface area, contributing to its thermal stability and adsorptive capabilities. The porous nature of wood ash and the unique structural characteristics of wood charcoal position them as promising candidates for various industrial applications, including construction, environmental remediation, and energy storage. This research underscores the importance of utilizing renewable biomass by-products, highlighting their role in advancing sustainable material practices and promoting environmental stewardship.
Keywords: 40 Engineering; 4016 Materials Engineering; 34 Chemical Sciences; 7 Affordable and Clean Energy; 13 Climate Action; Wood ash; Wood charcoal; Sustainable materials; Structural integrity; Adsorptive capacity